THE EXPERIENCE OF USING ARTIFICIAL INTELLIGENCE IN MAMMOGRAPHY BASED ON THE CLINICAL ADVISORY DIAGNOSTIC CENTER - Колпинский, Глеб Иванович; Вайман, Евгений Федорович; Шкарабуров, Александр Сергеевич; Вилкина, Екатерина Викторовна; Корабельников, Никита Сергеевич (Medicine in Kuzbass, 2024)
Digital technologies have firmly entered into modern radiation diagnostics, providing doctors with truly limitless opportunities to work with digital archives of medical images (X-ray, MSCT, MRI, ultrasound, PET) in terms of dynamic assessment of the development of the pathological process and the effectiveness of patient treatment, remote (telemedicine) counseling of images obtained by remote access. Meanwhile, the most responsible thing for doctors is the phased introduction of artificial intelligence (AI) technologies, which are entrusted with the functions of virtual evaluation of the received medical images, in other words, diagnosis. In the presence of the unconditional advantages of artificial intelligence: the speed of digital image processing, the release of the time of the diagnostician, the medical community is likely to face certain risks that must be eliminated in order to achieve the final goals within the framework of improving the quality and accessibility of medical care. Goal – Training of AI in the description of mammograms, assessment of opportunities for the introduction of AI tools in the description of mammograms. Materials and methods. Desk research. Results. Based on the systematization of information obtained during the preliminary study, the main positive and negative sides were identified when implementing AI tools in the diagnosis of breast diseases using the BI-RADS (Breast imaging-reporting and data system) system. Discussion. The introduction of AI into the system of diagnosis of breast diseases is accompanied by a certain range of risks associated with inaccuracy of data, data security and the ethical side of the issue. Conclusion. The collected and systematized data from the mammography rooms of the I.A. Kolpinsky Clinical Consulting and Diagnostic Center and the opinions of experts are valuable material for formulating recommendations on the introduction of AI tools in Kuzbass healthcare.